Advances in Artificial Intelligence - IBERAMIA 2008 11th Ibero-American Conference on AI, Lisbon, Portugal, October 14-17, 2008. Proceedings - Geffner, Hector; Prada, Rui; Machado Alexandre, Isabel; David, Nuno (Lecture Notes in Artificial Intelligence,, 2008)
This book constitutes the refereed proceedings of the 11th Ibero-American Conference on Artificial Intelligence, IBERAMIA 2008, held in Lisbon, Portugal, in October 2008. The 46 papers presented were carefully reviewed and selected from 147 submissions. The papers are organized in topical sections on Knowledge Representation; Planning and Scheduling; Constraint Satisfaction and Optimization; Probabilistic Reasoning; Machine Learning; Multiagent Systems; Natural Language Processing; Intelligent Information Systems and NLP; Robotics; and Applications.